2021
DOI: 10.1108/ijppm-08-2020-0441
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sustainable supply chain management and customer relationship management on organizational performance

Abstract: PurposeThis paper aims to assess the effect of sustainable supply chain management (SSCM) , competitive advantage (CA) and customer relationship management (CRM) on organizational performance (OP).Design/methodology/approachA self-administered questionnaire was employed in the present study as a research tool, consisting of 20 items. Information was gathered from 93 executives employed in the supply chain management (SCM) division of the multiple organizations in Chattogram, the commercial hub of Bangladesh an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 134 publications
5
47
0
Order By: Relevance
“…The current global supply chain environment is increasingly complex and dynamic, with globalization, digitization, and sustainability posing significant challenges to those involved. Customer relationship management (CRM) is now seen as a part of SCM, according to the work of Das and Hassan (2021), in part due to the impact external stakeholder pressure relating to sustainability has had on SCM overall. It is becoming increasingly beneficial for organizations to include CRM with SCM as the overall management strategies of both are interlinked.…”
Section: A Complex Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The current global supply chain environment is increasingly complex and dynamic, with globalization, digitization, and sustainability posing significant challenges to those involved. Customer relationship management (CRM) is now seen as a part of SCM, according to the work of Das and Hassan (2021), in part due to the impact external stakeholder pressure relating to sustainability has had on SCM overall. It is becoming increasingly beneficial for organizations to include CRM with SCM as the overall management strategies of both are interlinked.…”
Section: A Complex Systemmentioning
confidence: 99%
“…The research of Das and Hassan (2021) has indicated that SSCM does have a significant and positive effect on organizational performance and competitive advantage. This comes from both the beneficial effects of implementing sustainable practices, as well as the better management of supply chains the renewed focus on sustainability has caused.…”
Section: A Complex Systemmentioning
confidence: 99%
“…The increase in defense industries visitors is based on consumer or customer satisfaction provided by the defense industries . In addition, this is also based on the fact that consumers are changing their lifestyles and relying on e-commerce to fulfill their lives According to Dhanalakshmi et al (2020); Das, & Hassan (2021); Dragomirov, N. (2020) customer or consumer satisfaction is a level of a person's feelings which states the results of the comparison of the services or products he receives with what he expects. Therefore, to meet consumer satisfaction, there are several important factors to meet the satisfaction of these consumers.…”
Section: Introductionmentioning
confidence: 99%
“…The measured aspect of E-Service Quality or known as Online Service Quality is the degree to which a website or marketplace application can facilitate effectively and efficiently to make purchases, delivery and sales of both products and services. According to Das & Hassan (2021); Dragomirov, N. (2020); Haudi, et al (2021) According to Huda et al (2021); Hwihanus et al ( 2022) Besides E -Service Quality, the marketplace can also improve with Online Delivery Service Quality or E -Supply Chain Management. According to Huda et al (2021); Hwihanus et al (2022); Purwanto et al ( 2021) E -Supply Chain Management here is what is meant by consumer confidence in the delivery process that can be more effective and efficient.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the resource management approach, which included “waste management, energy management, and resource management,” was represented as a second-order construct. Waste management refers to practices such as element evaluation, the 4R program “reduce, reuse, recycle, and recover.” Das and Hassan ( 2021 ) focused on reducing resource usage and waste manufacturing. Energy management includes techniques such as “energy conservation programmes, frequent energy audits, the use of electricity devices, and the use of sustainable power to reduce energy use and its environmental impact” (Aray et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%